Academic Self-Efficacy Between Second-Year Nursing and Pharmacy Students at Basra Medical Institute: Comparative Study - Ali Suanid Alethar; Anmar Jabbar Alsaad; Maher Abdul Ameer Atiyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic self-efficacy plays a critical role in influencing students’ motivation, learning strategies, and academic performance. It reflects individuals’ belief in their ability to accomplish academic tasks effectively. Specific Background: Despite its significance, differences in self-efficacy levels among students from different health disciplines, particularly in Iraq, are understudied. Knowledge Gap: There is limited empirical evidence comparing academic self-efficacy between nursing and pharmacy students in Iraqi medical education settings. Aims: This study aimed to assess and compare academic self-efficacy levels among second-year nursing and pharmacy students at Basra Medical Institute and examine the influence of age and gender. Results: The findings revealed that pharmacy students had moderately higher academic self-efficacy (M = 2.62) compared to nursing students (M = 2.37). Age significantly influenced pharmacy students’ self-efficacy, favoring older students, while gender had no significant impact in either group. Novelty: This study provides the first comparative analysis of self-efficacy in these student groups within the Iraqi context and highlights discipline-specific challenges in applying knowledge. Implications: The results suggest the need for tailored interventions, such as mentorship, interactive learning, and psychological support programs, particularly for nursing students, to enhance academic self-confidence and performance.Highlight : Nursing students had lower academic self-efficacy compared to pharmacy students. Age significantly influenced pharmacy students' self-efficacy, but not for nursing students. Both groups showed high self-efficacy in leadership roles, yet struggled in practical application tasks. Keywords : Academic Self-Efficacy, Pharmacy Students, Nursing Students, Age, Gender